Transport communications understanding global networks enabling transport services - Tiffin, John (Kogan page, 2007)
The authors examine how existing modes of transport can be made more effective by the use of modern communications technology They show how possible future developments will continue to revolutionize transport systems, leading to better, cleaner, more cost effective systems.